Practices of Religious Education of Inner Tribe Children in Malaysia in Realizing SDGs 4 - Rahmi Maimunah; Dina Dahliana; Yusrial Yusrial; Hesti Leviana Sari; Hanis Syuhada Binti Abdul Rahim; Akmal Yandi (International Journal of Islamic Studies Higher Education, 2025)
This study analyzes the behavior of students at the Center for Indigenous Civilization Development in Pahang, Malaysia, focusing on the influence of family environment, cultural traditions, and technology. Using a qualitative case study approach, the research engaged 36 informants through direct observation, in-depth interviews, and both open and closed questionnaires. The findings indicate that family background and cultural traditions significantly shape students’ character and habits, while technology and social media provide positive impacts such as improved access to information but also create challenges, including tendencies to neglect academic responsibilities. Behavioral differences were observed across educational levels and gender, with early-level students relying more on teacher guidance and higher-level students demonstrating greater independence. The study recommends strengthening discipline, adopting active learning methods, and improving educational facilities to enhance learning quality, thereby contributing to the development of more effective and culturally relevant educational programs for indigenous students.